Pengaruh Harga, Lokasi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Bioskop Cinepolis Plaza Medan Fair - R. Switi Mallar; Yahya Tanjung S.T (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aims to determine the effect of price, location and service quality on customer satisfaction at the Cinepolis Plaza Medan Fair Cinema. The number of samples used in this research was 80 respondents. The data collection technique used in this research uses a questionnaire method, observation. The data sources used in this research use secondary and primary data sources. The testing techniques used in this research use research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results of this research show that the price variable has no effect on customer satisfaction, the location variable has a positive and significant effect on customer satisfaction and service quality has no positive and significant effect on customer satisfaction. Simultaneously, the variables price, location and service quality influence customer satisfaction. Price, location and service quality have a positive and significant effect on customer satisfaction at the Cinepolis Plaza Medan Fair cinema. Price has a positive and significant effect on customer satisfaction at the Cinepolis Plaza Medan Fair cinema. Location has no positive and insignificant effect on customer satisfaction at the Cinepolis Plaza Medan Fair cinema, Service Quality has a positive and significant effect on customer satisfaction at the Cinepolis Plaza Medan Fair cinema